2020
DOI: 10.3390/vaccines8030534
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination into the Dermal Compartment: Techniques, Challenges, and Prospects

Abstract: In 2019, an ‘influenza pandemic’ and ‘vaccine hesitancy’ were listed as two of the top 10 challenges to global health by the WHO. The skin is a unique vaccination site, due to its immune-rich milieu, which is evolutionarily primed to respond to challenge, and its ability to induce both humoral and cellular immunity. Vaccination into this dermal compartment offers a way of addressing both of the challenges presented by the WHO, as well as opening up avenues for novel vaccine formulation and dose-sparing strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 265 publications
(340 reference statements)
1
66
0
4
Order By: Relevance
“…In recent years, the major vaccination method has been intramuscular administration using a needle syringe. Intradermal administration, however, is also a promising vaccination method because dermal tissue is an easily accessible immune-rich environment that can induce both humoral and cellular immunity 26 . Tebas et al reported that intradermal Ebola GP DNA vaccine administration demonstrates humoral and cellular immunogenicity advantages compared with intramuscular administration 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the major vaccination method has been intramuscular administration using a needle syringe. Intradermal administration, however, is also a promising vaccination method because dermal tissue is an easily accessible immune-rich environment that can induce both humoral and cellular immunity 26 . Tebas et al reported that intradermal Ebola GP DNA vaccine administration demonstrates humoral and cellular immunogenicity advantages compared with intramuscular administration 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the major vaccination method has been intramuscular administration using a needle syringe. Intradermal administration, however, is also a promising vaccination method because dermal tissue is an easily accessible immune-rich environment that can induce both humoral and cellular immunity 26 . Tebas et al .…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cells are distributed in the epidermis and in the dermis, in particular around its vascularized areas. 7 DDCs capture antigens deposited in the dermis and migrate to regional lymph nodes, where the antigens are presented to T lymphocytes. Soluble antigens also migrate to lymph nodes, resulting in activation of B lymphocytes.…”
Section: Evidence From the Literaturementioning
confidence: 99%
“…Skin-targeted vaccines have the potential to be more immunogenic due to the immune-responsive nature of the skin compared to subcutaneous or intramuscular tissues targeted by prevailing vaccination routes [ 42 ]. These advantages, and the potential to obviate the cold-chain by stabilizing vaccine components in the delivery device, could enable minimally invasive delivery, self-administration, and economically advantageous refrigeration-free storage and distribution [ [42] , [43] , [44] , [45] , [46] ]. As such, skin-targeted vaccination using MAPs has received considerable attention, including recent efforts to develop MAP-delivered coronaviruses vaccines.…”
Section: Introductionmentioning
confidence: 99%